Baczko, the Enlightenment and Promises of Happiness - Andrea Marchili (Scienza & Politica)
The article thematizes the link between the Enlightenment and the French Revolution in Bronislaw Baczko’s work. Through the perspective of utopian language, which makes use of the resources of the symbolic and imaginative background, Baczko’s research attempts to restore the processual character of the Enlightenment and its materialization in the praxis of the French Revolution. The Enlightenment emerges there as an ambivalent, open, unfinished process, in relation to which 20th-century history has taken on a constructive and tragic role.